State of the World's Forests - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
FAO. 1999. 154 pp.ISBN 92 5 104193 8 $40.00 /E39FAO Sales and Marketing GroupViale delle Terme di Caracalla, 00100 Rome, ItalyFax: +39 06 57 05 33 60Email: publications-sales@fao.org